Pengaruh Rekrutmen, Latar Belakang Pendidikan Dan Seleksi Terhadap Kinerja Pegawai (Study Pada Pegawai Perum Perhutani Perencanaan Hutan Wilayah Bojonegoro) - Aulia Firma Hairera; Abdul Kodir Djaelani; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of recruitment, educational background and selection on the performance of study employees at Perum Perhutani Perencanaan Hutan Bojonegoro Region employees. This type of research used is quantitative research with the method of distributing questionnaires. The sample in this research was 38 respondents and data processing used the SPSS computer program. This research has met the requirements of validity and reliability. Analysis of the data used in this study is the classical assumption test, multiple linear regression, hypothesis testing and analysis of the coefficient of determination. The variables used in this study are performance variables (dependent), while the independent variables are recruitment, educational background, and selection of employee performance.The results of this study concluded that the variables Recruitment, Educational Background and Selection had a good effect simultaneously on Employee Performance and partially had a good effect on Recruitment and Background variables, but the Selection variable had the opposite direction on Employee Performance. Keywords: Employee Performance, Recruitment, Educational Background, and Selection.